PSYCHOPEDAGOGICAL AND FAMILY INTERVENTION IN AUTISM SPECTRUM DISORDER - Cristiane Florencio dos Santos, Márcia; de Oliveira Azevedo Silva, Juliana; dos Santos Oliveira, Valdineli; Maria da Silva Siqueira, Josivânia (Revista Gênero e Interdisciplinaridade, 2023)
This work consists of an attempt to present the main learning problems evidenced in the course of psychopedagogical therapies, directed at children with Autistic Spectrum Disorder (ASD) and in particular a case study. In which the reflection was analyzed specifically in the possibilities of interaction through workshops, finger painting and activities with geometric figures, with the objective of walking towards rescuing self-esteem as well as awakening an attractive learning with more meanings and the reflexes were analyzed and discussed in the school and family environment. This scenario raised the difficulties of inclusion of children with Autism Spectrum Disorder (ASD) and that their social insertion is possible in proportion to revering their world, believing that, due to their limitations, care should be more specific. In this context, it is understood that the psychopedagogue, together with professionals from other areas, are able to act in the cognitive and behavioral development of ASD carriers, during their school and family life, contributing in a unique way to independence in their daily lives.